2019
DOI: 10.1111/jth.14543
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptors 2 and 7 mediate coagulation activation and coagulopathy in murine sepsis

Abstract: Background Sepsis is a life‐threatening condition often manifested as marked inflammation and severe coagulopathy. Toll‐like receptors (TLRs) play a pivotal role in inflammation, organ dysfunction and mortality in animal sepsis. Objectives To investigate the role of TLR signaling in mediating sepsis‐induced coagulopathy (SIC) in a mouse model. Methods Polymicrobial sepsis was created by cecal ligation and puncture (CLP) or fecal slurry peritoneal injection. To quantify global clotting function, two viscoelasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…In sum, all that can be said in general about innate activation in sepsis is that TLR2, TLR4, TLR5, TLR7 and NLRP3 [102] can be, but are not necessarily, activated, while TLR9 may or may not be downregulated [103][104][105]. The same generalizations can be made about murine polymicrobial sepsis models [91,[106][107][108], suggesting that sepsis is not a single, definable disease [97]. Table 1 summarizes these data, demonstrating that cytokine release syndromes share only partial overlaps in their innate receptor activation profiles, which provides a possible clue as to why their cytokine release profiles also differ and, therefore, why it has been difficult to define a clear set of diagnostic criteria for them or to devise a comprehensive or universal approach to treatment.…”
Section: Synergistic and Antagonistic Receptor Activation Network Inmentioning
confidence: 84%
“…In sum, all that can be said in general about innate activation in sepsis is that TLR2, TLR4, TLR5, TLR7 and NLRP3 [102] can be, but are not necessarily, activated, while TLR9 may or may not be downregulated [103][104][105]. The same generalizations can be made about murine polymicrobial sepsis models [91,[106][107][108], suggesting that sepsis is not a single, definable disease [97]. Table 1 summarizes these data, demonstrating that cytokine release syndromes share only partial overlaps in their innate receptor activation profiles, which provides a possible clue as to why their cytokine release profiles also differ and, therefore, why it has been difficult to define a clear set of diagnostic criteria for them or to devise a comprehensive or universal approach to treatment.…”
Section: Synergistic and Antagonistic Receptor Activation Network Inmentioning
confidence: 84%
“…Previous studies have shown that the expression of ELANE is able to reflect the leukocyte function during sepsis, which is able to provide more prognostic information than leukocyte counting [21]. Brittney Williams et al found that TLR2 and TLR7 are involved in coagulation dysfunction in murine sepsis, which may be an important reason for the high mortality of sepsis [28].The regulatory axis of GDF / SMAD2 / SMAD3 in sepsis that can promote macrophage polarization toward M2 phenotype leading to immunosuppression, and activation of this regulatory axis may be associated with high lethality in sepsis [26]. CD3E, as part of the TCR-CD3 complex, is present on the surface of T-lymphocytes and plays an important role in adaptive immunity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lipoteichoic acid, a membrane component of Gram-positive bacteria, was shown to inhibit platelet aggregation in human platelets [ 201 ] and reduce platelet thrombus formation in vitro [ 202 ], which may not cause thrombotic complications, but could be of advantage to the bacteria that would not be trapped in a thrombus. In addition, TLR3 and TLR4 could be of particular importance in platelet responses during sepsis, because a deficiency in either of these receptors is associated with more severe thrombocytopenia during polymicrobial sepsis induced by a cecal ligation and puncture procedure, while TLR2- and TLR7-deficient mice displayed a less severe coagulopathy, suggesting a different pattern of TLR involvement in murine polymicrobial sepsis [ 203 ]. Finally, another innate immunity receptor, C-type lectin-like-2/CLEC-2, found on platelets could be beneficial during sepsis by downregulating inflammation and leukocyte infiltration in tissues and reducing organ damage, further illustrating that the contribution of platelets to sepsis pathophysiology is not unequivocal [ 204 ].…”
Section: Platelet Contribution To Pathogenesis Through Their Innate Immunity Receptorsmentioning
confidence: 99%